The Electrical Conductivity of Copper (I) iodide (CuI) Thin Films Prepared by Mister Atomizer - Amalina, M. N.; Ayib Rosdi, Zainun; N. A., Rasheid; Rusop, M. (IEEE, 2012)
In this paper, the copper (1) iodide (CuI) thin films were prepared by mister atomizer with different thickness. The effect of thickness of CuI thin films were done by varying the deposition flow rate and deposition time. The effects of thickness to its structural, electrical and optical properties were studied. The resistivity increases as the thickness of thin film increase with highest resistivity of 4.79 x 101 ȍ cm. The transmittance for most of the samples was transparent of above 80% in the visible wavelength. The transmittance and absorption coefficient was measured and then the energy gap was determined which shows the direct transition of n=2. The maximum band gap observed here is 2.82 eV for the thickest thin films. The observation on effect of thickness in this study shows that the increasing of thin film thickness increased the resistivity while the absorption coefficient decrease with slight rise of band gap w